2022
DOI: 10.1186/s13018-022-03315-x
|View full text |Cite
|
Sign up to set email alerts
|

miR-210-3p suppresses osteogenic differentiation of MC3T3-E1 by targeting brain derived neurotrophic factor (BDNF)

Abstract: Background and objective As an important mediator of intercellular interaction and formation of extracellular bone matrix, porous scaffolds are widely used for bone regeneration. Accumulating evidences demonstrate that microRNA are involved in the regulation of scaffolds-induced bone regeneration. Recently, we revealed that miR-210-3p was highly expressed during osteogenesis induced by HAG. In present study, we further explored the molecular mechanism underlying the effect of miR-210-3p on oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Thus, Li et al [ 35 ] found overexpression of mhesiR-133a-3p markedly inhibited the expression of osteogenesis-associated genes such as RUNX2 and OSX , reduced ALP activity and mineralization by targeting ankyrin repeat domain 44 (ANKRD44) in BMMSCs. Similarly, Deng et al [ 36 ] observed significant inhibition of osteogenic differentiation, cell migration, and cell proliferation in MC3T3-E1 cells due to miR-210-3p. This suppression was attributed to the direct targeting of brain-derived neurotrophic factor (BDNF) by miR-210-3p.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, Li et al [ 35 ] found overexpression of mhesiR-133a-3p markedly inhibited the expression of osteogenesis-associated genes such as RUNX2 and OSX , reduced ALP activity and mineralization by targeting ankyrin repeat domain 44 (ANKRD44) in BMMSCs. Similarly, Deng et al [ 36 ] observed significant inhibition of osteogenic differentiation, cell migration, and cell proliferation in MC3T3-E1 cells due to miR-210-3p. This suppression was attributed to the direct targeting of brain-derived neurotrophic factor (BDNF) by miR-210-3p.…”
Section: Discussionmentioning
confidence: 86%
“…54 Another study also found that miR-210-3p suppresses osteogenic differentiation of MC3T3-E1 by targeting brain derived neurotrophic factor. 61 No study has reported the relationship between miR-210 and osteogenic differentiation of hJBMSCs. This experiment will continue to investigate the role of miR-210 in osteogenic differentiation of hJBMSCs and create a new research direction for miR-210.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Li et al found that MiR-210-3p inhibits osteogenic differentiation and promotes adipogenic differentiation correlated with Wnt signaling in ERalpha-deficient rBMSCs . Another study also found that miR-210-3p suppresses osteogenic differentiation of MC3T3-E1 by targeting brain derived neurotrophic factor . No study has reported the relationship between miR-210 and osteogenic differentiation of hJBMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Its effect on osteoblasts depends on the dosage. Under physiological conditions, TNF-a promotes the migration and proliferation of osteoblasts by activating the p38/MAPK pathway (49). In contrast, under acute inflammatory conditions, excessive TNF-a inhibits osteoblastogenesis by inhibiting the Wnt pathway by regulating GSK3b (50).…”
Section: Osteogenesismentioning
confidence: 99%